Question
Solve for x . \[ -2(-2 x-2)+x+2=-9 \]
Ask by Cole Burgess. in the United States
Feb 03,2025
Real Tutor Solution
Tutor-Verified Answer
Answer
\( x = -3 \)
Solution
To solve the equation:
\[
-2(-2x - 2) + x + 2 = -9
\]
**Step 1: Distribute the \(-2\) across \((-2x - 2)\)**
\[
-2 \times (-2x) + (-2) \times (-2) = 4x + 4
\]
So, the equation becomes:
\[
4x + 4 + x + 2 = -9
\]
**Step 2: Combine like terms**
\[
4x + x + 4 + 2 = 5x + 6
\]
Now the equation is:
\[
5x + 6 = -9
\]
**Step 3: Isolate \(x\)**
Subtract 6 from both sides:
\[
5x = -9 - 6
\]
\[
5x = -15
\]
Divide both sides by 5:
\[
x = \frac{-15}{5} = -3
\]
**Solution:** \( x = -3 \)
Reviewed and approved by the UpStudy tutoring team
Like
error msg
Explain
Simplify this solution
Mind Expander
To solve for \( x \) in the equation \[ -2(-2x - 2) + x + 2 = -9, \] let's first simplify the left-hand side. Distributing \(-2\) gives: \[ 4x + 4 + x + 2 = -9. \] Now combine like terms: \[ 5x + 6 = -9. \] Next, we isolate \( x \) by subtracting \( 6 \) from both sides: \[ 5x = -9 - 6, \] \[ 5x = -15. \] Now, divide both sides by \( 5 \): \[ x = -3. \] So, the solution is \[ \boxed{-3}. \]